Trabalho e disputas por direitos na Sadia em Uberlândia (2000- 2010) - Santana, Fabiano Silva (2017)
In this work we investigate the historicity of class struggle in Sadia Alimentos SA, located in Uberlandia, Minas Gerais, between the years 2000 to 2010. We believe that the relationships woven together with the production processes are important to understand the nuances of the work within a productive context. In this perspective, we seek to highlight the changes in productive relations, the forms of sociability among the workers, and the transformations in the ways of life, from current characteristics of the work. Thus, we realize that the factory floor is where you create and reproduce meanings, expectations, values and feelings. It is in this sense that the sources were read in an attempt to identify the changes that pervade the lives of these workers inside and outside the factory, and guarantee senses in the search for work and right.